ANALISIS KETERBUKAAN INFORMASI AJB BUMIPUTERA 1912 TERKAIT KASUS KETERLAMBATAN PEMBAYARAN KLAIM ASURANSI PADA PEMEGANG POLIS (JATUH TEMPO 2017-2019) - Vinsensia Pale (2021)
This research is a qualitative research that aims to find out how the implementation of AJB Bumiputera 1912's information disclosure related to the case of late payment of insurance claims to policyholders has been carried out. This study uses an interpretive paradigm with an ethnomethodological approach. Data collection techniques were carried out by means of interviews, observation, and documentation. Informants in this study consisted of; AJB Bumiputera 1912 whose identity is kept secret and 3 policyholders who are retired Elementary School (SD) principals, retired High School (SMA) teachers, and Civil Servants (PNS) of the Agriculture Service who are policy holders of the AJB Bumiputera 1912 branch office in City X. The results of this study indicate that the management of the branch office of AJB Bumiputera 1912 in City X, especially regarding the management of claims payment information, has implemented the principles of transparency, accountability, responsibility, independence, as well as equality and fairness. The implementation of information disclosure related to cases of late payment of insurance claims to policyholders has been carried out by using the BP Info application to check the disbursement of insurance claims, the issuance of the press release of AJB Bumiputera 1912 on the website www.ajb.bumiputera.com, and the provision of a means to complain to policyholders in the form of a letter that forwarded to the head office of AJB Bumiputera 1912. However, in implementing the principles of corporate governance, the branch office of AJB Bumiputera 1912 in city X encountered problems in implementing the principle of transparency related to disseminating information on the development of late payment of insurance claims to policyholders. The obstacles faced by the AJB Bumiputera 1912 branch office in the city of X include; geographical constraints, psychological constraints of policyholders, time and place constraints, and limited information disclosed by insurance agents. Keywords: Corporate Governance, Late Payment of Insurance Claims, Information Disclosure